PENGARUH GOOD CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP KINERJA KEUANGAN - Rini Nurhasanah (Nusantara Hasana Berdikari, 2021)
Along with development of teh era of competition in companies from day to day increasing, one of wich is in banking companies which are financial institutions that collect public deposits and channel them back to the public in the form of credit or loans. To prosper the shareholders through financial performance and to improve the company’s performance, good and trustworthy good corporate governance is needed. In addition, the company also adopts a leverage policy so that the affectivity of the company runs smoothly. This study aims to determine the extent to which the level of good corporate governance and leverage on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. This study uses a quantitative approach in the form of numbers and the data used are secondary data. By using descriptive data analysis method, namely classical assumption test and hypothesis testing. Based on the results in this study, the partial test of good corporate governance that uses the indicators of the board of commissioners and the audit committee has an effect on financial performance, and leverage using the debt to asset ratio indicator affects financial performance, for financial performance using the ROA (return on assets) indicator.